دور العلاقات العامة في تحسين اداء الموظفين داخل المؤسسة الخدماتية - شوشة خضرة; فارسي زهراء (كلية العلوم الاجتماعية, 2021)
باللغة العربية: حًثهج يشكهت انذساست فً دٔس انؼالقاث انؼايت فً ححسٍٍ أداء انًٕظفٍٍ داخم انًإسست انخذياحٍت "يإسست احصاالث انجضائش سٍذي ػهً يسخغاَى " اػخًذَا فً دساسخُا نبهٕؽ األْذاف انًشجٕة ػهى يجًٕػت يٍ انخساؤالث حخًثم فً حساؤنٍٍ سئٍسٍٍٍ: ْم حهؼب انؼالقاث انؼايت دٔسا فً ححسٍٍ أداء انًٕظفٍٍ داخم انًإسست انخذياحٍت احصاالث انجضائش؟ يا ًْ انصؼٕباث ٔانًشاكم انخً حٕاجّ انؼًال ػُذ انقٍاو بًٓايٓا ٔانخً حؼٍق اداءْى انٕظٍفً داخم انًإسست انخذياحٍت؟ كًا اػخًذَا ػهى يجًٕػت يٍ األْذاف حًثهج فًٍا ٌهً: يؼشفت طبٍؼت َشاط انؼالقاث انؼايت بانًإسست انخذياحٍت احصاالث انجضائش فشع سٍذي ػهً بٕالٌت يسخغاَى. يؼشفت أبشص االشكال ٔانشسائم انً حسخخذيٓا انًإسست فانذاخم يغ انؼًال نخحسٍٍ أدائٓى انكشف ػٍ انًشاكم انخً ٌٕاجٓٓا انؼًال بانُظش ئنى طبٍؼت انؼالقاث انؼايت داخم انًإسست ٔحأثٍش رنك ػهى أدائٓى انٕظٍفً يؼشفت ارا كاَج انؼالقاث انؼايت كًًاسست داخم انًإسست ححفض ٔحشجغ انؼًال فً أداء ػًهٓى. ٔيٍ أجم اإلجابت ػهى ئشكانٍت بحثُا حى االػخًاد فً ْزا انبحث ػهى انًُٓج " أنٕصفً ْٔزا نكَّٕ األكثش يالئًت نًٕضٕع دساسخُا ٔاػخًذَا ػهى انًقابهت نجًغ انبٍاَاث ٔقذ قًُا باخخٍاس يجخًغ بحثُا فً ْزِ انذساست بُاء ػهى ابشاص طبٍؼت انًجخًغ ٔانًخًثم فً كم انًٕظفٍٍ فً يإسست احصاالث انجضائش " سٍذي ػهً " ٔػهٍّ فاٌ يجخًغ بحثُا يٍ َٕػٍت انذساست كَّٕ يجخًغ صغٍش.ملخص باللغة ال جنللزيةة: The problem of the study was the role of public relations in improving the performance of employees within the service institution "Algeria Telecom, Sidi Ali Mostaganem." In order to achieve the desired goals, we relied on a set of questions, represented by two main questions: _ Does public relations play a role in improving the performance of employees within the service organization, Algeria Telecom? _ What are the difficulties and problems that workers face when performing their tasks that hinder their job performance within the service institution? We also relied on a set of objectives represented in the following: Knowing the nature of public relations activity in the service institution, Algeria Telecom, Sidi Ali branch, in Mostaganem Knowing the most prominent forms and messages that the institution uses, and internally with the workers to improve their performance. Detecting the problems that workers face in view of the nature of public relations within the institution and its impact on their job performance. Knowing if public relations as a practice within the institution motivates and encourages workers to perform their work. In order to answer the problem of our research, this research was based on the "descriptive approach, and this is because it is the most appropriate to the subject of our study. We relied on the interview to collect data. We chose the community we researched in this study based on highlighting the nature of the society represented in all employees in the Algeria Telecom Corporation" Sidi Ali Therefore, our research community is of the type of study as it is a small community
Keywords: العلاقات العامة؛اداء الموظفين؛المؤسسات الخدماتية